Peran Strategis Lembaga Keuangan Syariah bagi Usaha Mikro Kecil Menengah (UMKM) dalam Mewujudkan Pembangunan Ekonomi - Istiqomah, Azizatul (Maliki Interdisciplinary Journal, 2025)
This article discusses the strategic role of Sharia Financial Institutions in supporting Micro, Small and Medium Enterprises (MSMEs) in Indonesia as part of sustainable economic development. Sharia Financial Institutions, which include Islamic banking, Islamic insurance, and Islamic mutual funds, have existed since the time of the Prophet PBUH and have experienced significant development since the first Islamic economic conference in Mecca in 1975. This study uses the literature review method to explore how Islamic Financial Institutions can provide access to financing in accordance with sharia principles, which is very important for MSMEs who often face difficulties in obtaining funds from conventional financial institutions. Research shows that Islamic financial institutions not only provide financing but also help MSME actors become more independent and competitive in the market. In addition, this article discusses the problems faced by Islamic financial institutions, such as building sufficient infrastructure and human resources in the digital era. Support from Sharia Financial Institutions is needed to encourage inclusive and sustainable economic growth, considering that MSMEs account for 61% of Indonesia's GDP and absorb 97% of the workforce. This article emphasizes that Sharia Financial Institutions and the government must work together to create policies that support the growth of MSMEs and increase financial inclusion. Therefore, it is hoped that Sharia Financial Institutions can continue to develop to achieve the socio-economic goals of the Indonesian nation.